The long-term neurodevelopmental outcomes of toddlers with SARS-CoV-2 infection in the neonatal period: a prospective observational study - Ezgi Yangin Ergon; Senem Alkan Ozdemir; Sinem Akbay Ak; Meltem Yenilmez; Buse Soysal; Oğuz Han Kalkanlı; Şebnem Çalkavur; Tülin Gokmen Yıldırım (BMC, 2024)
Abstract Background The effect of Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) virus in the neonatal period on developing brain is still unknown. This study aims to investigate the long-term neurodevelopmental outcomes of newborns exposed to SARS-CoV-2 & Delta variant. Methods At a tertiary referral center, a prospective observational cohort research was carried out. All babies who were equal to or more than 34 gestational weeks gestation and were admitted to the NICU between January 2021 and January 2022 due to SARS-CoV-2 infection (Delta - or Delta +) were included in the study. Infants who were hospitalized for non-SARS-CoV-2 reasons at similar dates and who had no history of invasive mechanical ventilation were incorporated as a control group using a 2:1 gender and gestational age match. Thirty infants were assigned to the study group and sixty newborns to the control group based on the sample size calculation. These toddlers' neurodevelopment was evaluated between the ages of 18 and 24 months using the Bayley-II scale. Results We enrolled 90 infants. SARS-CoV-2-positive infants had poorer psychomotor development index (PDI) scores and significantly greater mildly delayed performances (MDPs) at 18-24 months (PDI p = 0.05, MDPs p = 0.03, respectively). Delta variant showed statistically significant lower MDI and PDI scores (MDI p=0.03, PDI p=0.03, respectively). A smaller head circumference of SARS-CoV-2-positive toddlers was detected in the first year (p  < 0.001), which improved at the second age. Conclusion SARS-CoV-2-positive neonates revealed lower PDI scores and greater MDPs at 18th-24th months. The effect is most noticeable in Delta variant. Longer-term examination of neurodevelopmental outcomes and reevaluation of these children between the ages of 5 and 12 are critical.